NILAI-NILAI PROFIL PELAJAR PANCASILA DALAM TEKS CERPEN PADA BUKU SISWA BAHASA INDONESIA KELAS VII SMP - Sidiq, Achmad Sahrir; Septian Syarifudin, Albitar; Ilman Faqih, Fiyan (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
The implementation of character education on the Merdeka curriculum is reflected in the content of a Pancasila student in any learning by the teacher. The profile of Pancasila student is made up of six components of value that reflect the student's character according to the Pancasila values namely, faith in the almighty God and given a noble motive, reasoning critical, independent, creative, gotong-royong, and global inequality. These six values are then required to be implemented in reading materials. In this article, the Pancasila student value projections will be analyzed in the student book the Indonesian class VII SMP. This is important as a form of criticism of the text presented in the class VII SMP student book because it relates to the text content that should reflect the profile of the Pancasila student. Using data analysis techniques, the article will focus on the short stories text, since it is a student popularity. It is therefore expected to find a concrete form of the application of the Pancasila student profile value on a short stories text presented in the Indonesian class VII SMP. Results and findings following careful text analysis are the profile values of the Pancasila student have incorporated even stories presented very close to the noble character to be inherited.